Manajemen Berbasis Sekolah: Sejarah dan Strategi Implementasi Pada Satuan Pendidikan - Yusri A. Boko; Amrin Sibua (Jurnal Ilmiah Wahana Pendidikan, 2021)
Article 51 paragraph (1) of Law Number 20 of 2003 concerning Education System states: Management of early childhood education units, basic education, and secondary education is carried out based on Minimum Service Standards with the principle of School-Based Management (SBM). This article aims to discuss a brief history and strategy for implementing SBM in schools. The approach in this paper is literature study. The term MBS first appeared in the United States in 187, when people began to question the relevance of education to the demands of its development. In Indonesia, SBM was born as a school reform agenda, which was marked by the RI Law No. 22/1999 and the RI Law No. 25/1999 on Regional Autonomy. Strategies in implementing SBM include: 1) one of the strategies is to create conducive preconditions to be able to implement SBM, namely increasing the capacity and commitment of all school members, including the community and parents of students, 2) building a democratic, transparent school culture. , and accountable, 3) when the central government plays a more monitoring and evaluation role. This means that the central and local governments need to carry out joint activities in the context of monitoring and evaluating the implementation of SBM in schools, including the implementation of block grants in schools, 4) developing a model of school empowerment programs, not just carrying out SBM training, which is mostly fulfilled by providing school information. However, the development of MBS in America and Atlanta is certainly different from that in Indonesia because it depends on the government's "political will".